Trade Liberalization and Gender Wage Inequality: Panel ARDL Approach for Emerging Economies - Fatema, Farha; Li, Zhaohua; Islam, Mohammad Monirul (International Journal of Economics and Financial Issues, 2018)
This study examines the co-integration and causality direction between trade openness, as a proxy to liberalization, and gender wage gap in the emerging economies. In this study, we applied panel auto-regressive distributed lag (PARDL) model to identify the association between trade openness and gender inequality in wage and Granger causality test to analyze the causality directions between them for 1994-2014. The results of co-integration and ARDL analyses of the panel dataset indicate that trade openness and gender wage gap are cointegrated, and fully modified OLS (FMOLS) and pooled mean group (PMG) estimates results identified a positive association between trade openness and gender pay inequality in the emerging economies. The results Granger causality analysis specifies a unidirectional causality from trade openness to gender wage gap in both short-run and long-run which infers that trade openness significantly raises wage inequality between male and female in the emerging countries. Keywords: Trade openness; gender wage gap; Panel ARDL; Granger causality; unidirectional causality JEL Classifications: O50; F63; F14